Database design and development by adopting open archival information system (OAIS) for Bahagian Arkib dan Muzium / Syahiidatulkamaliah Mohamad Kamal - Mohamad Kamal, Syahiidatulkamaliah (2012)
This research describe about how to develop the Archival System database for Bahagian Arkib dan Muzium. Database will be developing followed standard that has been used by National Archive which is by adopting Open Archival Information System (OAIS). Process on designing database will start with overlook on the Information Model that has been suggested by previous research. Based on the Information Model, the requirement of the database will be determine and it will be used to designing the database. Designing the database that followed the National Archive standard is to make information shareable. By that, Bahagian Arkib dan Muzium will be able to transferred inactivated information that been kept more that 5 years to National Archive of Malaysia.